ROA codex. - Lippard, Lucy.; Braeckman, Johan (Tielt : Uitg. Lannoo N.V., 2019)
Fascinated by nature, the anonymous muralist and street artist ROA is inspired by the beauty of its non-human inhabitants. With great attention to detail, ROA draws over-sized black and white creatures of endemic or endangered species on buildings around the world, from Moscow to Mexico City, and from Los Angeles to London. His subjects are frequently survivors; scavengers, rodents, and unusual animals that thrive in their particular milieu.
boek
Keywords: ROA